Exploring perceptions, attitudes and beliefs of Thai patients with type 2 diabetes mellitus as they relate to medication adherence at an out-patient primary care clinic in Chiang Mai, Thailand - Jiraporncharoen, Wichuda (BMC Fam Pract, 2020)
BACKGROUND: Within the sphere of diabetes self-management, much emphasis has been placed on medication adherence. There has been a shift in thinking about medication adherence, moving from “compliance” and historically paternalistic models of care, to seeking better ways of characterizing dynamic and complex relationships that determine medication adherence and diabetes control. This study sought to understand the relationship between patient’s attitudes and medication adherence for oral anti-diabetics in Thailand. METHODS: In-depth interviews of patients with type 2 diabetes mellitus, taking oral anti-diabetic drugs, at the out-patient clinic run by the Department of Family Medicine, Chiang Mai University between May and December 2016. Thematic analysis followed the WHO framework for medication adherence in chronic disease to explore patient’s attitudes and their influence on medication compliance. RESULTS: Of 24 patients, 9 were men. The mean age was 62 years (SD 8.9 years). 67% had high compliance. Four themes were identified as important factors related to medication adherence: attitudes toward disease, attitudes toward treatment, attitudes toward family support and attitudes toward health care team. Specifically, symptoms at diagnosis, understanding and acceptance in taking medication, the presence of family support and the perception of concern by the doctor relate to improved medication compliance. CONCLUSIONS: Medication adherence in Thai patients with diabetes requires support from both the health care providers and the family. The patient’s perception of the doctor’s concern creates greater patient trust in the health care team. This trust, along with family support, helps deepen patients’ understanding of the disease, accept the chronic nature of their disease, and engenders a positive attitude towards taking medication that can improve medication adherence.